Glutathione-ascorbic acid redox cycle and thioredoxin reductase activity in the digestive tract of Leptinotarsa decemlineata (Say) - Krishnan, Natraj; Kodrík, Dalibor; Kłudkiewicz, Barbara; Sehnal, Frantisek (Insect biochemistry and molecular biology, 2009)
In view of the antioxidant role of glutathione (GSH) and ascorbic acid (AA), we have examined capacity of the GSH-AA redox cycle in relation to oxidative stress effects in the midgut of the Colorado potato beetle Leptinotarsa decemlineata. Adult gut harbors a higher capacity to cope with oxidative stress than the larval gut. Protein carbonylation was pronounced in the wall of anterior larval midgut and was generally lower in the food digest than in the gut wall. Restriction of oxidative stress effects in anterior gut lumen manifested by lipid peroxidation and protein carbonylation is interpreted as a mechanism favoring digestion and absorption in the posterior midgut. Presence of high GSH in the posterior midgut and AA in both posterior and anterior midguts of adults points to higher utility of the GSH-AA redox system in limiting oxidative stress to manageable levels. The presence, gene expression and activity of thioredoxin reductase (TrxR) were demonstrated for the first time in L. decemlineata which was markedly higher in the anterior than in the posterior midgut in both stages. It is probably central to the maintenance of reduced GSH levels in the whole gut, despite a GSSG/2GSH redox potential tending towards oxidizing ranging from -183.5 to -124.4mV. Glutathione-dehydroascorbate reductase (G(DHA)R) activity was markedly augmented in adult gut compared with larva, pointing to a more efficient conversion of dehydroascorbate (DHA) to AA. Also, ascorbate peroxidase (APOX) activity was significantly elevated in all gut compartments of adult except the wall of posterior midgut. The results emphasize the potential importance and role of the GSH-AA redox cycle as a defense strategy against oxidative stress in the gut of L. decemlineata.
Keywords: kyselina askorbová; Gene Expression; Glutathione; Thioredoxin-Disulfide Reductase; Oxidation-Reduction; brouci; Gastrointestinal Tract; oxidace-redukce; exprese genu; thioredoxin-disulfidreduktasa; Ascorbic Acid; gastrointestinální trakt; glutathion; Animals; Oxidative Stress; zvířata; oxidační stres; Coleoptera